Detecting and sharing praxeologies in solving interconnecting problems: some observations from teacher education viewpoint Détecter et partager les praxéologies dans la résolution de problèmes d'interconnexion: quelques observations du point de vue de la formation des enseignants - Kondratieva, Margo (Educação Matemática Pesquisa Revista do Programa de Estudos Pós-Graduados em Educação Matemática, 2020)
Abstract This paper discusses praxeologies available at different levels of schooling in view of a problem, which permits multiple solutions ranging from elementary to more advanced mathematical approaches. Solutions of the problem produced by mixed groups of K-12 teachers included numerical, pictorial and algebraic methods, and allowed observing possible paths within a finalized activity of study and research. They also gave some insights regarding teachers’ readiness to support the continuity of students’ praxeological development, and more generally, the potential within teachers’ educational backgrounds to pursue the new paradigm of questioning the world. Keywords: Teacher education, Praxeological development, Mathematical problems with multiple solutions. Résumé Ce texte discute les praxéologies disponibles à différents niveaux de la scolarité pour résoudre un problème qui permet des résolutions multiples, depuis des approches élémentaires aux plus avancées. Les résolutions proposées par un groupe mixte d’enseignants de l’école élémentaire jusqu’au lycée ont employé des méthodes numériques, graphiques et algébriques, et permettent d’observer les parcours possibles d’une activité finalisée d’étude et de recherche. Elles nous laissent aussi percevoir la capacité des enseignants pour soutenir la continuité du développement praxéologique des élèves, et plus généralement le potentiel résultant de la formation des enseignants à poursuivre le nouveau paradigme du questionnement du monde. Mots-clés: formation des enseignants, développement praxéologique, problèmes mathématiques aux solutions multiples.